DIFFUSION AND ADOPTION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN SOUTH AFRICAN TELECENTRES: SELECTED TELECENTRES IN KWAZULU-NATAL - Mbatha, Blessing (Mousaion: South African Journal of Information Studies, 2016)
This study investigated the usage and types of information and communications technologies (ICTs) accessible to community members in four selected Thusong Service Centres (TSCs or telecentres) in KwaZulu-Natal (KZN). The telecentres that participated in the study were: Nhlazuka, Mbazwane, Dududu and Malangeni. The study was informed by Rogers’ (1995) Diffusion of Innovations (DoI) theory. Through a survey, four TSCs were purposively selected. A questionnaire was used to collect data from community members in the four telecentres involved. The data collected was tabulated under the various headings and presented using tables, frequencies, percentiles and generalisations with the help of the Statistical Package for the Social Sciences (SPSS). The results indicated that a variety of ICT tools have been adopted in the TSCs to provide the local community with the much-needed access to information and improved communication. The government should ensure that adequate varieties and levels of ICT competence are offered to all the citizens. In conclusion, there is a need for sufficient and coherent government policies regulating the training of the local community to use these ICTs effectively.